Perencanaan Tenaga Kerja Makro: Studi Kasus Implementasi Program Kartu Pra-Kerja Sebagai Strategi Peningkatan Kualitas Sumber Daya Manusia di Indonesia - Ahmad Salafuddin Bahri; Dita Ayu Oktavia Ramadani; Niken Ira Yuliastuti; Tita Andari Sukma; Aldila Putri Rahma; Richa Septia Ariyanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Indonesia currently faces strategic opportunities through the demographic bonus, but major challenges also arise in macro workforce planning. One of the main problems is the mismatch between the skills of education graduates and the demands of the world of work, which are increasingly complex due to the acceleration of digital transformation and the impact of the COVID-19 pandemic. To address this, the government launched the Pre-Employment Card Program in 2020 as an effort to develop the quality of human resources through vocational training and entrepreneurship. This study aims to evaluate the implementation of the Pre-Employment Card Program as part of a macro workforce planning strategy and examine its impact on improving work competencies, reducing unemployment, and improving the economic quality of the community. The methodology used is a descriptive qualitative approach with secondary data analysis from various sources. Based on the research, the program has succeeded in expanding access to digital skills training, reducing open unemployment, and improving the work readiness of the young workforce. However, challenges such as the digital divide in underdeveloped areas and uneven quality of training are still a concern.